Web Profil Sebagai Media Promosi di CV Activa Amanah Karya - Adi Guno, Sepbianto; Nugroho, Novianto; Hendrianto, Yogi; Wijayanto, Hendro; Dwi Raharja, Bayu (Redtech Putra Benua, 2024)
CV. Activa Amanah Karya serves various IT product and service needs required by users. Among them are providers of IT technology security facilities, CCTV installation, computer equipment, laptops, laptop services, networking. CV. Activa Amanah Karya is ready to carry out installations in buildings, factories, campuses, schools, offices, shophouses, boarding houses, warehouses, and so on. CV. Activa Amanah Karya is committed to providing the best solutions and services for IT customers/users. In CV. Activa Amanah Karya has 4 employees who each have their own duties according to their respective expertise. CV. Activa Amanah Karya itself has a very strategic location because it is in a densely populated area. The aim of this activity is to promote information about CV. Activa Amanah Karya via Web profile or via website